Persistence and change of Afghan-German economic cooperation - The case of the New Baghlan Sugar Company - Kreutzmann, Hermann; Schütte, Stefan (ERDKUNDE, 2010)
Rebuilding a national economy in a conflict situation poses a host of challenges, and this holds true especially for contemporary Afghanistan. The case of the New Baghlan Sugar Company is taken as a precedent for analysing continuity and change in Afghan-German relations and in an agro-industrial enterprise that was conceived in the 1930s and has survived until today. Today, as in the past, cooperation partners have included the Afghan government and Afghan private entrepreneurs as well as the German government and German private entrepreneurs. Sugar beet production and its processing as a joint-effort to substitute sugar imports in Afghanistan were propagated as a profitable undertaking carried out in the spirit of modernisation. The study shows the constraints from the early days as well as the challenges for the public-private partnership of today. A prominent symbol of Afghan-German cooperation is taken as a case in point for elaborating on the current challenges and constraints. Despite substantial subsidies, the full operation of the factory has not been achieved and sugar beet production remains far below expectations. Barriers to development remain high three years into the project, and the comparative study highlights difficulties along the production chain and discusses the findings in the framework of national and local politics.